Tanggung Jawab Negara terhadap Hak Asasi Manusia dalam Perspektif Filsafat Hukum - Zahrah Rani'ah Delyananda; Irwan Triadi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This article analyzes the state's responsibility in fulfilling human rights from a legal philosophy perspective, which raises the main issue of the imbalance between the ideal justice in the constitution and its reality. This study aims to determine the causes of the fulfillment of human rights in Indonesia, which is still limited to formalities even though the regulations are clear, and how legal philosophy can provide a basis for evaluating this situation. The research method used is normative-philosophical, with conceptual, legislative, and historical approaches, as well as qualitative-prescriptive analysis of Aristotle's theory of justice, Kant's deontological ethics, legal positivism, and the values of social justice in Pancasila and the 1945 Constitution. The results of the study show that overly dominant legal positivism has resulted in the fulfillment of human rights often stopping at legality on paper rather than real justice. The state has also not been optimal in carrying out its ethical function of fulfilling, protecting, and respecting human rights through distributive, corrective, and affirmative policies. There is an urgent need to integrate moral values, governance ethics, and social justice principles in the interpretation and implementation of public policy. These results emphasize the need for a more ethical, responsive, and substantive justice-oriented legal paradigm shift so that the fulfillment of human rights in Indonesia can be truly meaningful and in line with the mandate of the constitution.